2006
DOI: 10.1021/ic060246q
|View full text |Cite
|
Sign up to set email alerts
|

Triiodide Quenching of Ruthenium MLCT Excited State in Solution and on TiO2 Surfaces:  An Alternate Pathway for Charge Recombination

Abstract: The excited states of [Ru(bpy)2(deeb)](PF6)2, where bpy is 2,2-bipyridine and deeb is 4,4'-(CO2CH2CH3)2-2,2'-bipyridine, were found to be efficiently quenched by triiodide (I3-) in acetonitrile and dichloromethane. In dichloromethane, I3- was found to quench the excited states by static and dynamic mechanisms; Stern-Volmer analysis of the time-resolved and steady-state photoluminescence data produced self-consistent estimates for the I3- + Ru(bpy)2(deeb)2+ <==> [Ru(II)(bpy)2(deeb)2+,(I3-)]+ equilibrium, K = 51… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 34 publications
2
38
0
Order By: Relevance
“…It should be noted here that the observed k q from both steady state and time resolved measurements gave the similar values, indicates the observed quenching is due to a diffusive process. This k q value is very comparable with previously reported k q values for ruthenium complexes [23], meaning that the quenching rate constant of pathway II is similar for both ruthenium and PSF molecules. Further, the thermodynamic driving force (ΔG et ) of electron transfer between PSF and iodide can be verified according [42,43] to the well-known Rehm-Weller expression (Eq.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…It should be noted here that the observed k q from both steady state and time resolved measurements gave the similar values, indicates the observed quenching is due to a diffusive process. This k q value is very comparable with previously reported k q values for ruthenium complexes [23], meaning that the quenching rate constant of pathway II is similar for both ruthenium and PSF molecules. Further, the thermodynamic driving force (ΔG et ) of electron transfer between PSF and iodide can be verified according [42,43] to the well-known Rehm-Weller expression (Eq.…”
Section: Resultssupporting
confidence: 90%
“…However, on a semiconductor surface such as SnO 2 the iodide quenching is not able to compete with the charge injection since the latter process is an ultrafast process that occurs in few femtoseconds-nanoseconds time scale. Later, Meyer et al has demonstrated Ru(II) polypyridyl metal-toligand charge transfer (MLCT) excited states effectively oxidize iodide [21][22][23]. Ion-pairing interactions between I À and ruthenium complex, greatly facilitated excited state iodide oxidation in dichloromethane and, to a lesser extent, in acetonitrile.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a negative shift of two peaks of ∼1,350 and 1,250 cm −1 from 2.2 to 2.1 V was observed that is due to the formation of I 3 − (ref. 25). Therefore, I 2 was reduced to I 3 − after discharging to 2.1 V. After that, those two peaks began to positively shift upon further discharge to 1.5 V. The positive shift could be attributed to the reduction of I 3 − to I − (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The practice of omitting the colored I 3 -component from the supporting electrolyte, and replacing it with nonredox active species such as ClO 4 -, for example, when carrying out timeresolved studies of the electron transfer dynamics of these cells is generally done out of convenience, due the high optical density associated with solutions that are ∼ 0.05 M in I 3 -. However, recent work suggesting that I -can quench the excitedstate of certain sensitizers, 24,25 a process that would have a significant impact on the overall injection yield and therefore on the maximum current density, compelled us to consider whether the injection dynamics observed in the absence of the I 3 -/I -redox couple were reflective of processes occurring in the functional device.…”
Section: Discussionmentioning
confidence: 99%